Keefektifan Model Pembelajaran Problem Solving Berbantuan Video Interaktif Terhadap Kemampuan Pemecahan Masalah Siswa Kelas III SDN Gedawang 01 Semarang - Ardita, Serandha; Putra, Lisa Virdinarti (Universitas PGRI Semarang, 2023)
The purpose of this study is to determine the effectiveness of the problem solving learning model on the problem-solving ability of grade III students of SDN Gedawang 01 Semarang. This type of research is quantitative research with a problem solving learning model using interactive videos. The population in this study was grade III SDN Gedawang 01 and grade III SDN Gedawang 02 Semarang totaled 56 students. Meanwhile, the sample, namely class III SDN Gedawang 01, was 28 students. Data collection techniques in the form of observations, questionnaires, interviews and tests. The technical data analysis used is the Independent Test sample T-test and the Simple Linear Regression Test. The results showed that: there was a difference in the average problem solving ability of students between the control class and the experimental class, which can be seen from 1) Independent Test T-test sample and obtained thitung ttabel (3.83 2.13) with a sig value. (2 -tailed) i.e. 0.0010.05 then Ho is rejected and Ha is accepted. 2) There is an effectiveness of interactive video-assisted problem solving learning models, which can be seen from the Simple Linear Regression Test and obtained a signification level of F 67.195, sig:0.000a 0.05. So it can be concluded that the interactive video-assisted problem solving learning model is effectively used to improve the problem-solving ability of grade III students of SDN Gedawang 01 Semarang.